Influence of specific collagen peptides and 12-week concurrent training on recovery-related biomechanical characteristics following exercise-induced muscle damage—A randomized controlled trial - Bischof, Kevin; Stafilidis, Savvas; Bundschuh, Larissa; Oesser, Steffen; Baca, Arnold; König, Daniel (Frontiers in Nutrition, 2023)
It has been shown that short-term ingestion of collagen peptides improves markers related to muscular recovery following exercise-induced muscle damage. The objective of the present study was to investigate whether and to what extent a longer-term specific collagen peptide (SCP) supplementation combined with a training intervention influences recovery markers following eccentric exercise-induced muscle damage. Fifty-five predominantly sedentary male participants were assigned to consume either 15 g SCP or placebo (PLA) and engage in a concurrent training (CT) intervention (30 min each of resistance and endurance training, 3x/week) for twelve weeks. Before (T1) and after the intervention (T2), eccentric muscle damage was induced by 150 drop jumps. Measurements of maximum voluntary contraction (MVC), rate of force development (RFD), peak RFD, countermovement jump height (CMJ), and muscle soreness (MS) were determined pre-exercise, immediately after exercise, and 24 and 48 hours post-exercise. In addition, body composition, including fat mass (FM), fat-free mass (FFM), body cell mass (BCM) and extracellular mass (ECM) were determined at rest both before and after the 12-week intervention period. Three-way mixed ANOVA showed significant interaction effects in favor of the SCP group. MVC (p = 0.02, ηp² = 0.11), RFD (p<0.01, ηp² = 0.18), peak RFD (p<0.01, ηp² = 0.15), and CMJ height (p=0.046, ηp² = 0.06) recovered significantly faster in the SCP group. No effects were found for muscle soreness (p = 0.66) and body composition (FM: p = 0.41, FFM: p = 0.56, BCM: p = 0.79, ECM: p = 0.58). In summary, the results show that combining specific collagen peptide supplementation (SCP) and concurrent training (CT) over a 12-week period significantly improved markers reflecting recovery, specifically in maximal, explosive, and reactive strength. It is hypothesized that prolonged intake of collagen peptides may support muscular adaptations by facilitating remodeling of the extracellular matrix. This, in turn, could enhance the generation of explosive force. ClinicalTrials.gov (ID: NCT05220371)